Is a conclusion premature? Commentary on the article by O. Starn - Thurner, Mark (1992)
First of all, I'm glad someone wrote this article. And second, I am pleased that Allpanchis decided to translate it in order to open a critical debate. Starn's controversial argument is basically correct. In addition, it is carefully developed. I agree with the central proposal: it is necessary to break with certain ideological traditions of an "orientalist" nature.